Non-typhoidal Salmonella soft-tissue infection after gender affirming subcutaneous mastectomy case report. Issue 1 (31st December 2023) - Barger, Branden T.; Pakvasa, Mikhail; Lem, Melinda; Ramamurthi, Aishu; Lalezari, Shadi; Tang, Cathy
Abstract: We present a case of a 32-year-old transgender male who underwent chest masculinization, complicated by purulent soft tissue infection of bilateral chest incisions. Cultures tested positive for non-typhoidal Salmonella, methicillin-resistant Staphylococcus aureus, and Pseudomonas aeruginosa . Herein, we discuss multiple factors contributing to the complexity of treating this patient's clinical course.